2011
DOI: 10.1007/s12311-011-0285-y
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Nicotinic Cholinergic Receptors are Intrinsic to the Cerebellum: Implications for Diverse Functional Roles

Abstract: Although recent studies have delineated the specific nicotinic subtypes present in the mammalian cerebellum, very little is known about their location or function within the cerebellum. This is of increased interest since nicotinic receptors (nAChRs) in the cerebellum have recently been implicated in the pathology of autism spectrum disorders. To begin to better understand the roles of these heteromeric nAChRs in the cerebellar circuitry and their therapeutic potential as targets for drug development, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Multiple studies have confirmed the role of cerebellum in auditory function 20 , 21 , nicotinic cholinergic receptors are present in this brain region 35 , and hearing loss is one known symptom of cerebellar stroke syndromes 36 . On these bases, our PheWAS results can be explained by the following hypothesis: smokers with rs113288603 * T have increased CYP2A6 expression in cerebellum that results with consequent altered brain exposure to nicotine and some of its metabolites, and thus protects these subjects from the nicotine-induced changes associated with age-related hearing loss.…”
Section: Discussionmentioning
confidence: 95%
“…Multiple studies have confirmed the role of cerebellum in auditory function 20 , 21 , nicotinic cholinergic receptors are present in this brain region 35 , and hearing loss is one known symptom of cerebellar stroke syndromes 36 . On these bases, our PheWAS results can be explained by the following hypothesis: smokers with rs113288603 * T have increased CYP2A6 expression in cerebellum that results with consequent altered brain exposure to nicotine and some of its metabolites, and thus protects these subjects from the nicotine-induced changes associated with age-related hearing loss.…”
Section: Discussionmentioning
confidence: 95%
“…Several subtypes of neuronal nicotinic receptors have been reported to be expressed in rat cerebellum including, in decreasing order of abundance, α4β2 > α3β4 > α3β2β4 > α3α4β2 = α4β2β4 (Turner and Kellar, 2005), and recent studies have indicated that most of these receptors are located in cells within the cerebellum including granule cells, Purkinje cells and interneurons, rather than on afferents (Turner et al, 2011). Studies have also indicated the presence of α7 subunits in mostly perisynaptic regions in the granule cell layer, albeit in very low abundance (Caruncho et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Nonspecific binding was determined in the presence of 300 μM nicotine, and specific binding was defined as the difference between total binding and nonspecific binding. Binding data were expressed as fmol/mg tissue (Turner et al 2011a; Turner et al 2011b). …”
Section: Methodsmentioning
confidence: 99%